2004
DOI: 10.1128/iai.72.7.4275-4278.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Pyocyanin Is Critical for Lung Infection in Mice

Abstract: Pseudomonas aeruginosa secretes copious amounts of the redox-active phenazine, pyocyanin (PCN), during cystic fibrosis lung infection. PCN has been shown to interfere with a variety of cellular processes in cultured lung epithelial cells. Here, by using two respiratory tract models of infection, we demonstrate that PCN mediates tissue damage and necrosis during lung infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
298
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(311 citation statements)
references
References 20 publications
10
298
0
3
Order By: Relevance
“…The opportunistic pathogen P. aeruginosa produces phenazines, antibiotics that contribute to virulence not only by directly damaging host tissues but also by enhancing pseudomonad fitness during host colonization (18,21,22,46,55). In particular, P. aeruginosa is well known for production of the bright blue phenazine pyocyanin, which contributes to the coloration of sputum and pus associated with infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opportunistic pathogen P. aeruginosa produces phenazines, antibiotics that contribute to virulence not only by directly damaging host tissues but also by enhancing pseudomonad fitness during host colonization (18,21,22,46,55). In particular, P. aeruginosa is well known for production of the bright blue phenazine pyocyanin, which contributes to the coloration of sputum and pus associated with infections.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa is an opportunistic pathogen that causes biofilmbased infections with devastating effects (16). This Gram-negative bacterium synthesizes phenazines, redox-cycling antibiotics that affect redox homeostasis and gene expression in both the producer and hosts (17)(18)(19)(20)(21)(22). Several years ago, our group showed that pyocyanin (5-N-methyl-1-hydroxyphenazine), the most wellknown P. aeruginosa phenazine (23), activates the redox-active transcription factor SoxR and thereby induces expression of a small regulon that includes the RND (resistance-nodulation-division) efflux pump-encoding operon mexGHI-opmD (hereafter referred to as "mex") (24,25).…”
mentioning
confidence: 99%
“…The bacterium secretes a large number of products that contribute to virulence. These include type III-secreted exotoxins that disrupt the cytoskeleton and lyse the cells, as well as proteases, phospholipase, rhamnolipids, and hemolysin (3)(4)(5)(6)(7)(8). In addition, P. aeruginosa produce and secrete the blue pigment pyocyanin (PYO), which is found in the sputum of patients with CF and bronchiectasis at concentrations up to 100 M; this is responsible for the blue-green color often observed in CF sputum (4,5,9,10).…”
mentioning
confidence: 99%
“…Structurally simple phenazines such a phenazine-1-carboxylic acid (PCA) and its hydroxy and carboxamide derivatives are produced by beneficial strains of Pseudomonas on the roots of plants, where they have a critical role in suppressing fungal pathogens (2,3) and can contribute to the ecological competence of the strains that produce them (4). The antibiotic properties of pyocyanin, the blue phenazine synthesized in human tissues by the opportunistic pathogen Pseudomonas aeruginosa, were first reported in the late 1890s, although interest now focuses on its role as a virulence determinant in chronic and acute lung disease (5,6). The antibiotic, antiparasitic, and antitumor activities of naturally occurring phenazine compounds also have stimulated interest in the development of synthetic analogues tailored to particular therapeutic applications, but progress has been limited by the lack of efficient and generally applicable methods for the synthesis of substituted phenazines (1).…”
mentioning
confidence: 99%